Klassifikaciâ v russkih i angliiskih naučnyh tekstah - Kotûrova, Mariâ P.; Krasavceva, Nadežda А. (Stylistyka, 1994)
The authoresses distinguish in the logical-cognitive structure of classification а numЬer of elements, and then discuss the ways - implicit and explicit - of their representation in Russian and English texts. They also carry out - from the epistemological point of view - the typology of classifications appearing in academic texts.